Product assembly sequence optimization based on genetic algorithm - Yasin, Azman; Puteh, Nurnasran; Daud, Ruslizam; Omar, Mazni; Syed-Abdullah, Sharifah Lailee (Engg Journals Publications, 2010)
Genetic algorithm (GA) is a search technique used in computing to find approximate solution to optimization and search problem based on the theory of natural selection. This study investigates the application of GA in optimizing product assembly sequences. The objective is to minimize the time taken for the parts to be assembled into a unit product. A single objective GA is used to obtain the optimal assembly sequence, exhibiting the minimum time taken. The assembly experiment is done using a case study product and results were compared with manual assembly sequences using the ‘Design for Assembly’(DFA) method. The results indicate that GA can be used to obtain a near optimal solution for minimizing the process time in sequence assembly. This shows that GA can be applied as a tool for assembly sequence planning that can be implemented at the design process to obtain faster result than the traditional methods.